Maternité et carrière: indentité et gestion des sphere d’activités - Spain, Aremelle; Bédard, Lucille (Canadian Journal of Counselling and Psychotherapy, 2011)
The authors present a synthesis of their studies on motherhood and career as experienced by two groups of women according to their age at the birth of their first child. Professional aspects prior to pregnancy, motivations and decision to become a mother, and strategies used to combine professional and family lives were scrutinized to shed light on the vocational development of these women. The evaluation of their life scenarios was also taken into account. From the analysis of results, two conceptual models have emerged, underlying the importance of a global, open and flexible perspective for understanding the vocational development of women. Identity, as an organizing principle of this development, is based mainly on affiliation processes. Recommendations for career counsellors are suggested.